Minimally Invasive Robotic Kidney Transplantation for Obese Patients Previously Denied Access to Transplantation. Issue 3 (25th February 2013) - Oberholzer, J.; Giulianotti, P.; Danielson, K. K.; Spaggiari, M.; Bejarano‐Pineda, L.; Bianco, F.; Tzvetanov, I.; Ayloo, S.; Jeon, H.; Garcia‐Roca, R.; Thielke, J.; Tang, I.; et al.
<x xml:space="preserve">Abstract</x> The authors report results on a new robotic kidney transplantation technique for obese patients that has comparable patient outcomes compared to an open procedure.